Hepatic Epigenetic Reprogramming After Liver Resection in Offspring Alleviates the Effects of Maternal Obesity - Simino, Lais A. de Paula; Fontana, Marina Figueiredo; de Fante, Thais; Panzarin, Carolina; Ignacio-Souza, Letícia Martins; Milanski, Marciane; Torsoni, Marcio Alberto; Desai, Mina; Ross, Michael G.; Torsoni, Adriana Souza (Frontiers in Cell and Developmental Biology, 2022)
Obesity has become a public health problem and during pregnancy, it can lead to an increased risk of gestational complications and permanent changes in descendants. Offspring of obese dams (HF-O) are at increased risk of developing non-alcoholic fatty liver disease (NAFLD), even in the absence of high-fat diet (HFD) consumption. NAFLD is a chronic disease that can require liver resection. Liver regeneration is necessary to preserve the organ function. A range of pathways is activated in the liver regeneration process that are under epigenetic control. We investigated whether microRNAs modulation in the liver of HF-O would impact gene expression of Hippo, TGFβ, and AMPK pathways and tissue regeneration after partial hepatectomy (PHx). Female Swiss mice fed a standard chow or a HFD before and during pregnancy and lactation were mated with male control mice. Offspring CT-O and HF-O weaned to CT diet until d56 were submitted to PHx surgery. Prior to the surgery, HF-O presented alterations in miR-122, miR-370, and Let-7a expression in the liver compared to CT-O, as previously shown, as well as in its target genes involved in liver regeneration. However, after the PHx (4h- or 48h-), differences in gene expression between CT-O and HF-O were suppressed, as well as in hepatic microRNAs expression. Furthermore, both CT-O and HF-O presented a similar regenerative capacity of the liver within 48h. Our results suggest that survival and regenerative mechanisms induced by the partial hepatectomy may overcome the epigenetic changes in the liver of offspring programmed by maternal obesity.